2009
DOI: 10.1002/asna.200811128
|View full text |Cite
|
Sign up to set email alerts
|

Temporal behaviour of global perturbations in compressible axisymmetric flows with free boundaries

Abstract: The dynamics of small global perturbations in the form of a linear combination of a finite number of non-axisymmetric eigenmodes is studied in the two-dimensional approximation. The background flow is assumed to be an axisymmetric perfect fluid with adiabatic index γ = 5/3 rotating with a power law angular velocity distribution Ω ∝ r −q , 1.5 < q < 2.0, confined by free boundaries in the radial direction. The substantial transient growth of acoustic energy of optimized perturbations is discovered. An optimal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This is done without referring to modal solutions what can be quite an involved task, especially in complex flows. For example, Zhuravlev & Shakura (2009) and Razdoburdin & Zhuravlev (2012) treated the optimals in the form of finite linear combinations of neutral acoustic modes in a quasi-Keplerian torus. The obtained optimal perturbation corresponds to a wave packet localised initially in the vicinity of the outer boundary of torus and moving towards the inner boundary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done without referring to modal solutions what can be quite an involved task, especially in complex flows. For example, Zhuravlev & Shakura (2009) and Razdoburdin & Zhuravlev (2012) treated the optimals in the form of finite linear combinations of neutral acoustic modes in a quasi-Keplerian torus. The obtained optimal perturbation corresponds to a wave packet localised initially in the vicinity of the outer boundary of torus and moving towards the inner boundary.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done, for example, by means of the singular value decomposition of the relevant matrix exponential projected onto the orthonormal basis, look Schmid & Henningson (2001). Butler & Farrell (1992) use this method to study the optimal transient growth in classical Couette, Poiseuille and Blasius boundary layer flows, Mukhopadhyay et al (2005) use it to investigate Keplerian flow in local approximation and Zhuravlev & Shakura (2009) and, subsequently, Razdoburdin & Zhuravlev (2012) apply it to study the global optimal growth in quasi-Keplerian torus with free boundaries. However, this strategy entails all technical difficulties related to calculation of modes and eigen-frequencies.…”
Section: Methods Of Lagrange Multipliersmentioning
confidence: 99%
“…In lieu of this, Ionnaou & Kakouris [8] reported in their study that stochastic forcing was found to lead to persistent activity with angular momentum transported outward. More recently, Zhuravlev & Shakura [31] applied optimal perturbation strategy to two-dimensional sub-Keplerian toroidal configurations. They found that optimal perturbations giving rise to substantial TG are composed of certain combinations of non-axisymmetric eigenmodes.…”
Section: Introductionmentioning
confidence: 99%
“…Matching (14) for the expansion of the WKBJ solution (11) in the vicinity of x 1 and x 2 gives the zero phase ϕ 0 = −nπ/2 and the dispersion relation…”
Section: Calculation Of Modesmentioning
confidence: 99%